PENANGANAN TAWURAN PELAJAR DITINJAU DARI FILSAFAT ILMU BIMBINGAN KONSELING - Riska Willyanti Handayani; Najlatun Naqiyah; Mochamad Nursalim (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
Recently, student brawl behavior increased and even resulted in fatalities. As a consequence, offenders generally receive a suspension or are expelled from school. Based on the perspective of the guidance and counseling concept, these suspensions are contrary to the role and function of guidance and counseling at schools. This article aims to find the notion of intervention student brawls in terms of guidance and counseling philosophy of science. The method used is a literature review of e-books, 30 articles from journals, online encyclopedias, and dictionaries. The analysis was conducted by comparing ideas from each journal and integrating the results to make new conclusions. Results of the study show that in terms of the philosophy of science, a school counselor can implement guidance and counseling services to deal with student brawls. This study suggests that school leaders need to look at the intervention of student brawls from the disciplinary approach of guidance and counseling. For school counselors, the topic of guidance services provided to students to prevent student brawls includes managing emotions, conflict resolution, and self-efficacy. Whereas in counseling services, peace counseling strategies can be applied.